Adaptation among farmers towards climate change in rubber plantation / Muhammad Hafizzuddin Adnan - Adnan, Muhammad Hafizzuddin (Faculty of Plantation and Agrotechnology, 2016)
Climate change means annual temperature of the earth has swung up and down by several degrees Celsius over the past million years. At Malaysia climate change is the most environmental threats of the 21 st centuries. Climate change may bring about an increase in the frequency and intensity of extreme weather events, such as, droughts, storms and floods. Adaptation among farmers towards climate change in rubber plantation will be conducted to find the most factor that influence the adaptation among farmers towards climate change and also to determine the relationship between factor and to analyze respondents demographic profile. A simple random technique was used to select the sample 120 rubber smallholders from Jasin district. Data were collect through interview and questionnaire which are get from selected respondent.Through descriptive analysis, gender, age, race and education of the respondent has been identified specifically. Subsequently, correlation is performed to find out which factor influence the independent variable and has strong relationship towards the dependent variable Through correlation, extension agent that influence independent variable which have moderate relationship toward the dependent variable of 0.401 (r = 0.401, P <0.01). After correlation done regression was carried out. Factor most influence the independent variable and dependent variable which is yield of 0.588 (beta value = 0.588, P <0.005). For the conclusion yield are the main factor that contribute the adaptation among farmers towards climate change.